Perangkat Lunak Pencarian Apotek Menggunakan Metode Item Based Collaborative Filltering Dan Algoritma Floyd Warshall - Ari Muzakir; R.M Nasrul Halim; Andri Wijaya (Journal of Software Engineering Ampera, 2020)
Pharmacy is a health service that is very important for the community, this means that this is very much related to public health. To facilitate the community in finding the right and fast pharmacy with the best recommendations and shortest routes and several alternatives to the location of the pharmacy. This study aims to create software that makes it easier for people to find pharmacies based on alternative routes and other information related to the pharmacy located in the city of Palembang. This software uses the Floyd Warshall Algorithm as the shortest path algorithm and the Item-based collaborative filtering method for selecting items based on the rating given by the user. The system development method used is the prototype method. This research produces pharmacy location search software with alternative routes along with general information related to the pharmacy